VR 360 as an Alternative for Virtual-Based Practicum Learning with Stereoscopic View - Ary Budi Warsito; Eliando Eliando; Muhamad Yusup (CCIT (Creative Communication and Innovative Technology) Journal, 2021)
School education especially on primary school have a big impact to the children. Good and right education can sharpening the brain and influence the student with good attitude. Every information that attractive and easy to understanding is very important to give big impact for every primary school student, it also can provide a pleasant learning experience for these students. Therefore, this research develops a smartphone application that can provide a pleasant experience in learning knowledge of the surrounding environment from objects with virtual reality technology. To display these objects, a 360 ° panoramic image is used or a 2048px width 1024px width with a wide viewing angle (360 degrees) and this can be done by teachers to make the image or search for material sources on the internet. This technology allows students to see objects virtually. In use, this study requires a VR headset as a device for visualizing stereoscopic displays but it does not need installation because it is enough to access a smartphone browser then it will work. The system is designed using the spiral method as a process model and uses a-frame in application development. The interface can be run on the Android operating system. In making this application using the html programming language, laravel framework and a-frame framework.